USE OF ALTERNATIVE ENERGY SOURCES IN IMPROVING THE IMAGE OF COMPANIES IN THE MARKET - KOSAR, Nataliia; DEMKO, Mariana; KOLISNYK, Valeriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the influence of the use of alternative energy on the formation of a positive image of companies in the conditions of the energy crisis caused by the war in Ukraine. The use of renewable energy sources has become not only a critical step for achieving energy independence, but also an important aspect of corporate social responsibility, which contributes to increasing their competitiveness in the market. A review of scientific and analytical publications shows that despite the rapid development of the "green" energy sector, the issues of developing effective marketing strategies in this area remain open and require further research. In connection with the hostilities in Ukraine, energy infrastructure facilities suffered significant destruction, which created additional challenges for stable energy supply. According to the estimates of the World Bank, the total losses are significant, which emphasizes the importance of ensuring energy security as a strategic direction of the country's economic development. The article examines the experience of EU countries, in particular the REPowerEU initiative, which aims to achieve the share of renewable energy sources at the level of 45% by 2030. In Ukraine, the development of alternative energy is supported through national programs, such as the National Renewable Energy Action Plan, aimed at stimulating the use of environmentally friendly sources. Particular attention is paid to marketing approaches that can help companies position their brand as environmentally responsible. Among such strategies stand out personalized communications with customers, implementation of real environmental initiatives, organization of educational events such as webinars or trainings, as well as cooperation with local communities, which contributes to the growth of public trust. The use of such methods allows companies to attract environmentally conscious consumers, forming a strong connection between the brand and its audience. The authors also emphasize that an innovative approach to marketing, the integration of environmental values into business processes and the creation of long-term partnerships with customers can ensure sustainable development and stable competitive advantages for companies operating in the field of renewable energy. In modern conditions, "green" energy not only contributes to the protection of the environment, but also becomes a significant factor in increasing consumer loyalty. Companies that show concern for the environment receive additional opportunities for development, consolidating their image as progressive and socially responsible players on the market.
Keywords: alternative energy; renewable energy sources; energy security; environmental initiatives; competitive advantages; sustainable development; corporate image; social responsibility; marketing strategies